Hybrid mouse–prokaryotic DNA (cytosine-5) methyltransferases retain the specificity of the parental C-terminal domain - Pradhan, Sriharsa (Oxford University Press, 2000)
The mouse (cytosine-5) DNA methyltransferase (Dnmt1) consists of a regulatory N-terminal and a catalytic C-terminal domain, which are fused by a stretch of Gly-Lys dipeptide repeats. The C-terminal region contains all of the conserved motifs found in other cytosine-5 DNA methyltransferases including the relative position of the catalytic Pro-Cys dipeptide. In prokaryotes, the methyltransferases are simpler and lack the regulatory N-terminal domain. We constructed three hybrid methyltransferases, containing the intact N-terminus of the murine Dnmt1 and most of the coding sequences from M.HhaI (GCGC), M.HpaII (CCGG) or M.SssI (CG). These hybrids are biologically active when expressed in a baculovirus system and show the specificity of the parental C-terminal domain. Expression of these recombinant constructs leads to de novo methylation of both host and viral genomes in a sequence-specific manner. Steady-state kinetic analyses were performed on the murine Dnmt1–HhaI hybrid using poly(dG–dC)·poly (dG–dC), unmethylated and hemimethylated oligonucleotides as substrates. The enzyme has a slow catalytic turnover number of 4.38 h(–1) for poly(dG–dC)· poly(dG–dC), and exhibits 3-fold higher catalytic efficiency for hemimethylated substrates.